KANTIAN VIEWS OF EMPIRICAL TRUTH - GOLDBERG, Nathaniel (Studia Universitatis Babeș-Bolyai Philosophia, 2023)
Let a Kantian view of empirical truth be any view according to which the truth of empirical claim depends on the truth of non-empirical claims, because subjects (consciously or not) constitute the empirical when applying the non-empirical to experience. Historically the most important such view is Immanuel Kant’s. It is not the only. Rudolf Carnap, Thomas Kuhn, and Donald Davidson held such views. Conversely, Willard van Orman Quine’s view was contrastingly instructive. My aim is to briefly sort all this out in search of lessons about the nature of empirical truth generally.